2021
DOI: 10.33448/rsd-v10i12.20280
|View full text |Cite
|
Sign up to set email alerts
|

Construction 4.0: Industry 4.0 enabling technologies applied to improve workplace safety in construction

Abstract: Industry 4.0, the new production paradigm, has been arousing the interest of researchers around the world, due to its potential for improvements for companies, however little has been studied of its potential in the construction industry. This paper aims to identify which enabling technologies of Industry 4.0 can be applied to improve job security in civil construction. The methodology adopted was literature review, followed by field study / research with interviews with specialists, to identify the possibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Similarly, Dalenogare et al (2018) found that Industry 4.0 technologies helped companies to attain higher performance and it is positively linked with the estimated industrial aids. Likewise, Júnior et al (2021) mentioned that Industry 4.0 increased the work safety in the manufacturing industries, reduced accidents at work as well as collaborated in innovation. Moreover, Cimini et al (2020) concluded that Industry 4.0 technologies develop new job profiles and create a higher level of technical competencies at the organizational level.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Dalenogare et al (2018) found that Industry 4.0 technologies helped companies to attain higher performance and it is positively linked with the estimated industrial aids. Likewise, Júnior et al (2021) mentioned that Industry 4.0 increased the work safety in the manufacturing industries, reduced accidents at work as well as collaborated in innovation. Moreover, Cimini et al (2020) concluded that Industry 4.0 technologies develop new job profiles and create a higher level of technical competencies at the organizational level.…”
Section: Introductionmentioning
confidence: 99%
“…Virtual reality -Characterized by participation in a virtual environment and external observation creating an immersive experience, allowing the user to feel present in a virtual universe (Soares Júnior et al, 2021;Wen and Gheisari, 2020). CPS -Integrates technologies, promoting interconnections and interdependencies between physical components and networked cyber components (Satyro et al, 2017;Soares Júnior et al, 2021).…”
Section: Industry 40 Technologiesmentioning
confidence: 99%
“… Computer simulation – Also called digital twins, special software can reproduce the layout of an area, to study crane handling, movements, interference and others, trying to avoid potential problems in the processes (Hu et al , 2017; Li et al , 2012). Robotics – Collaborative robots can help in the handling of materials and processes, reducing human efforts and risks to worker health (Soares Júnior et al , 2021). Augmented reality – Through this technology, virtual objects can be taken to the physical environment, expanding the real environment, allowing humans to interact with them (Chen et al , 2020b; Soares Júnior et al , 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a technological and organizational culture change that involves risks, which grow as companies find themselves in advanced technological stages [75,76,79,94]. Companies that are in the Industry 1.0 or 2.0 stage should consider introducing automation technology and information technology first into the production process to reach the Industry 3.0 standard first, in order to reduce investments, risks and prepare the organizational culture.…”
Section: The Proposed Modelmentioning
confidence: 99%